TREATMENT OF ELLIS CLASS II FRACTURES IN MAXILLARY CENTRAL INCISORS CAUSED BY TRAUMA ON A 9 YEARS OLD BOY - Marissa Edyana; Heriandi Sutadi (Faculty of Dentistry, Universitas Indonesia, 2015)
Dental trauma in childhood and adolescence is a common accident, with the most accident-prone time is between 9 and 10 years old. Boys are affected almost twice than girls and the maxillary central incisors are the most affected. This report describes an Ellis class II fracture in maxillary central incisors caused by trauma on a 9 years old boy. The case was treated by pulp capping and restored by composite material.